EFFECT OF CYCLIC LOADING ON VELOCITY VALUE IN UNIAXIAL COMPRESSIVE STRENGTH TEST - Lanaya Windiani, Audy
Mining activities have an impact, one of which is changes in the characteristics of the surrounding rocks. Changes in rock characteristics occur because rocks are subjected to cyclic loading and unloading pressures. Cracks in the rock mass that experience cyclic loading can change the ultrasonic wave velocity. Therefore, it is necessary to analyze the effect of cyclic loading on the ultrasonic wave velocity of rocks. The rock samples in this study have different lithologies, consisting of Magnetite, Skarn, Diorite, Limestone, Granite, Tuff, and Altered Diorite. The research started with physical properties test, ultrasonic wave propagation speed test, UCS (Unconfined Compressive Strength) test and uniaxial loading unloading test of the rock samples. In the unloading loading test, the rock sample was given a variation of compressive force of 40-80% of the compressive strength (UCS) value. Afterwards, data processing is carried out and it is observed whether the loading and unloading loads affect the ultrasonic wave propagation speed and Young's Modulus values of the rock samples. The research findings indicate several significant outcomes. Firstly, there exists a positive relationship between rock density and ultrasonic wave propagation speed, suggesting that higher rock density corresponds to higher ultrasonic wave velocities. During loading, Vp experiences an increase ranging from 4.46% to 70.07% from its initial value. On the other hand, during unloading, Vp experiences a decrease ranging from 5.82% to 33% from its initial value. The decrease in Vp indicates the presence of cracks in the rock, while the increase in Vp indicates crack closure, the research shows that higher rock density leads to higher ultrasonic wave velocity, while higher porosity leads to higher changes in Vp. Loading-unloading tests affect the presence of cracks in the rock and influence the value of Young's Modulus.Lastly, the Young's Modulus value, which represents the stiffness of the material, was also affected by loading-unloading cycles. It was observed that the Young's Modulus value increased with an increase in the number of loadingunloading cycles.